2016
DOI: 10.21664/2238-8869.2016v5i1.p104-127
|View full text |Cite
|
Sign up to set email alerts
|

Enzimas Extracelulares de Solos de Cerrado como Bioindicadores de Qualidade em Áreas Agricultáveis em Goiás, Brasil

Abstract: A conversão de áreas nativas de Cerrado para a implantação de lavouras altera as propriedades físico-químicas e bioquímicas do solo. Neste estudo buscou-se compreender o efeito da sazonalidade do tipo de manejo utilizado para plantio de cana-de-açúcar sobre a atividade de hidrolases e oxirredutases. Amostras de solo de Cerrado nativo e solos convertidos a lavouras de cana-de-açúcar sob diferentes tipos de manejo foram submetidos a avaliações físico-química, biológica e bioquímica. A implantação de monoculturas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…This behavior can be attributed to the high TOC values observed in these systems. The higher the organic carbon content is, the higher the β-glucosidase enzyme values (Zago et al, 2016). In addition, the values of β-glucosidase in the IPF and PAS systems might be strongly related to the presence of grasses, since these plants usually have a dense root system that is mostly formed by fast-decomposing thin roots.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior can be attributed to the high TOC values observed in these systems. The higher the organic carbon content is, the higher the β-glucosidase enzyme values (Zago et al, 2016). In addition, the values of β-glucosidase in the IPF and PAS systems might be strongly related to the presence of grasses, since these plants usually have a dense root system that is mostly formed by fast-decomposing thin roots.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolases (EC 3.-) and oxidoreductases (EC 1.-) are the most studied classes of enzymes when evaluating SOM transformation and nutrient cycling processes [26,27]. These transformations of SOM and nutrient cycling enable the assimilation of simple molecules by microorganisms and plants through the roots [28]. Enzymes recognized in the literature for participating in nutrient cycling and SOM transformation that were found in the soils in this study are listed in Table 4.…”
Section: Functional Similarity Of Enzymes Of Soil Organisms During Re...mentioning
confidence: 95%
“…In the present study, important hydrolases were found, such as cellulose hydrolysis (EC 3.2.1.4) in R4 and NS, and glycosides hydrolysis such as beta-glucosidase (EC 3.2.1.21) in NS and alpha-glucosidase (EC 3.2.1.20) in R4. The first randomly hydrolyzes the cellulose molecule, releasing oligosaccharides of varying degrees of polymerization, whereas the enzymes beta-glucosidase (EC 3.2.1.21) and alpha-glucosidase (EC 3.2.1.20) break down low-molecular-mass oligosaccharides to produce monosaccharides, the main energy source for soil microorganisms [28,38]. Thus, we can observe in the R4 and NS soils enzymes involved in the complete transformation of cellulose, an organic compound that contains a relevant C stock necessary for the growth and survival of soil microorganisms [39].…”
Section: Protein Functional Analysis In the Community Of Soil Organismsmentioning
confidence: 99%
“…O potencial de transformação de nutrientes ou de fontes de energia específicas pode ser acessado ao se examinar essas enzimas do solo (MIRALLES et al, 2012). Estas transformações da MOS possibilitam a assimilação de moléculas simples pelos microrganismos e pelas plantas através das raízes (ZAGO et al, 2016).…”
Section: Enzimas Do Solo Ciclagem De C E Atividade Microbianaunclassified
“…Tabela 2 -Exemplos de oxidoredutases e hidrolases identificadas na metaproteômica de RAD Bastida et al (2014),Zago et al (2016). eAdetunji et al (2017).As oxidoredutases 1.2.1.12, 1.1.1.40, 1.1.1.42 são espécies de desidrogenases, suas atividades catalíticas de oxidação da matéria orgânica ocorrem no interior celular participando de vias metabólicas.…”
unclassified